Woody plant diversity and structure of shade-grown-coffee plantations in Northern Chiapas, Mexico - Soto-Pinto, Lorena (2001)
Shade-grown coffee is an agricultural system that contains some forest-like characteristics. However, structure and diversity are poorly known in shade coffee systems. In 61 coffee-growers’ plots of Chiapas, Mexico, structural variables of shade vegetation and coffee yields were measured, recording species and their use. Coffee stands had five vegetation strata. Seventy seven woody species mostly used as wood were found (mean density 371.4 trees per hectare). Ninety percent were native species (40 % of the local flora), the remaining were introduced species, mainly fruit trees/shrubs. Diametric distribution resembles that of a secondary forest. Principal Coordinates Analysis grouped plots in four classes by the presence of Inga, however the majority of plots are diverse. There was no difference in equitability among groups or coffee yields. Coffee yield was 835 g clean coffee per shrub, or ca. 1 668 kg ha-1. There is a significant role of shade-grown coffee as diversity refuge for woody plants and presumably associated fauna, as well as an opportunity for shade-coffee growers to participate in the new biodiversity-friendly-coffee market.